(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
Contemporary teaching should be real, rich and relevant. Changes in this direction that can be observed in higher education in Poland result from the requirements of the job market, students’ expectations, the need to adapt to the goals of the Bologna Process, as well as demands by educators. Considering the declining interest in studying (which is seen especially in the humanities), universities try to present their educational offer in the most attractive way to compete successfully with other universities. All of these changes can be seen on several levels: the decisions of the government, of the universities, faculties and institutes, and in the everyday work of the teachers. The paper describes these problems in relation to publishing education. Websites of universities offering courses on publishing are analyzed and the educational offer of the LIS Institute of the University of Wroclaw is presented in details. Examples of proven methods and useful educational resources and new allies are proposed.